1992
DOI: 10.1103/physrevlett.69.367
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of hydrodynamics in the classical 1D Heisenberg model

Abstract: Extensive spin-dynamics simulations have been performed to study the dynamical behavior of the classical Heisenberg chain at infinite temperatures and long wavelengths. We find that the energy and spin show distinctly different dynamics in the isotropic system. The energy correlation function follows the classical diffusion theory prediction, namely, it decays exponentially with q 2 t. In contrast, the spin correlation function is found to decay exponentially as q 2A2 t\nt, implying a logarithmically divergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 25 publications
0
36
1
Order By: Relevance
“…Another subsequent numerical work in this direction [16] however claimed that although energy diffusion is normal, spin diffusion has an anomalous behavior. [17].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Another subsequent numerical work in this direction [16] however claimed that although energy diffusion is normal, spin diffusion has an anomalous behavior. [17].…”
mentioning
confidence: 98%
“…Although the phenomenology of spin diffusion is an old concept [3,4], its validity in classical Heisenberg model has been vigourously debated in recent times. Although much effort [13][14][15][16][17][18][19][20] has been devoted to understand whether spin diffusion in this system is normal or anomalous, a convincing conclusion is yet to be reached. Settling this question is not only conceptually important e.g., in understanding transport properties of spin systems, but also has direct implications in routinely performed experiments e.g., NMR and ESR in magnetic compounds [5][6][7][8][9].…”
mentioning
confidence: 99%
“…These systems have been extensively studied, e.g., in the context of the spin diffusion problem [15][16][17], but their Lyapunov spectra have not yet been computed. Finite classical spin systems are also known to exhibit nontrivial integrable limits [18].…”
mentioning
confidence: 99%
“…In a recent Letter [1], de Alcantara Bonfim and Reiter investigated the infinite-temperature spin dynamics of the classical isotropic Heisenberg chain with emphasis on the spin-diffusion hypothesis by extensive numerical simulations. In particular, they found that their data for the spin-correlation function C(q,t) are well fitted by…”
mentioning
confidence: 99%